Perbandingan Pencapaian Belajar Bahasa Inggris Antara Anak Laki-Laki Dan Perempuan Dalam Program Bimbingan Belajar Bahasa Inggris Di Desa Kubang Utara Sikabu - Sandra Dewi; Wilda Yuliana; Mayla Safira Faizah; Difia Astri; Destin Dwi Mayasari; Mario Kurniawan (CV. ITTC INDONESIA, 2025)
This study was motivated by the implementation of an English tutoring program as part of the Community Service Program (KKN) by Universitas Negeri Padang in Period II of 2025, held in Kubang Utara Sikabu Village, Lembah Segar District, Sawahlunto City. The program aimed to improve basic English skills of elementary school-aged children through a fun and participatory learning approach. During the activity, the researcher observed differences in learning achievement between male and female students. Therefore, this study was conducted to determine whether there was a statistically significant difference between the two groups. The research employed a quantitative approach with a comparative design. Participants consisted of 16 children, 8 males and 8 females. Data were collected from post-test scores and analyzed using the non-parametric Mann-Whitney U test due to the data not meeting the assumptions of normality and homogeneity. The results showed no significant difference in English learning achievement between male and female students (p > 0.05). These findings suggest that the applied learning approach successfully created an equitable learning environment for all participants. The implication of this study highlights the importance of adaptive and inclusive teaching strategies to support successful learning without gender bias, particularly in the context of community-based non-formal education.